A well-organized graphene nanostructure for versatile strain-sensing application constructed by a covalently bonded graphene/rubber interface. Issue 8 (12th February 2018) - Guo, Quanquan; Luo, Yongyue; Liu, Jize; Zhang, Xinxing; Lu, Canhui
Abstract : A well-organized graphene nanostructure was developed for the versatile strain-sensing application via constructing a covalently bonded interface between graphene and a rubber matrix. Abstract : Graphene/rubber nanocomposites have attracted increasing attention for their fantastic applications in varied wearable electronics. However, the mechanical and functional properties of graphene/rubber nanocomposites are often limited by their weak interfacial interactions, such as ionic and hydrogen bonding. Here, we propose a covalently bonded graphene/rubber nanocomposite with a well-organized graphene nanostructure for versatile strain-sensing applications. Briefly, biological phytic acid was chosen as a covalent-bonding bridge to co-crosslink graphene oxide nanosheets and epoxidized natural rubber chains via the ring-opening reaction of epoxy groups. Benefiting from the covalently bonded interface, the obtained nanocomposite exhibited dramatically enhanced mechanical properties. Compared with the sulfur-cured sample, the tensile strength and elongation at break increased by 67.43% and 116.55%, respectively. Moreover, the covalent linkage facilitates the formation of a well-organized graphene network, which remarkably enhances the sensitivity and stability of the as-prepared strain sensors. The resultant sensors can monitor both large-scale and tiny human motion and exhibit great potential in the application of sign language recognition. This covalently bonded graphene/rubber interface opens the door to tailored design and low-cost fabrication of well-organized graphene nanostructures for multifunctional applications in electronic sensors, electromagnetic shielding materials, actuators for artificial muscles, etc .